Attributes for a Congruous Architectural Model - Patra, Bikash; Goray, Nawin Kumar; Kapuganti, Chitti Babu (Integrated Journal for Research in Arts and Humanities, 2022)
Now a days, architects and architecture students avoid using physical handmade models though it is a widely accepted and most prominent tool to understand and explain architectural design concepts. Physical handmade models play an essential role in converting conceptual ideas to working and working levels to design finalization and presentation for architectural design, structural design, interior design, and product design. Availability of inadequate skill to make models, excess time consumption, extensive effort, cost of model making materials, lack of knowledge about suitable material, lack of know-how about model making tools force the students of architecture to avoid using the physical model to explain or understand design. Any single model may not be appropriate for all the requirements. Each model needs to have a particular goal. The architect needs to finalize the scale, material, and tools with proper scrutiny to achieve the goal. To prepare an appropriate model for a particular purpose, one should have a thorough knowledge of model making skills or techniques, a sense of proportion, materials, tools, finishing materials. In certain times and some areas, suitable materials may not be available. In that case, the architect has to improvise and create materials using printers and using other tools. This paper discusses steps to prepare a model, criteria for selecting material and tools, and strategies to prepare an appropriate model.